Ways of Optimization Intensive Care in Patients with Infection Diseases - T. M. Zubik; K. V. Kozlov (Журнал инфектологии, 2014)
Intensive care of patients with infectious diseases, as part of the resuscitation, in our country took root in clinical practice on stages – from the treatment of very severe forms of some infections (nosological approach) to differentiated treatment depending on the clinical and pathogenic syndromes critical states (internosological approach). Based on the analysis of intensive therapy in 1387 patients with various infections identified the main syndromes of critical states: infectious and toxic encephalopathy, toxic shock, dehydration syndrome (shock), acute respiratory, hepatic and renal failure. Shows the frequency of their development or threat for the most common diseases. In modern conditions, improve the efficiency of treatment of patients with extremely severe forms of infectious diseases can be achieved by preventive measures – preventive intensive therapy in the presence of high-risk factors, urgent and emergency measures in the infectious disease department at the methodological and direct participation of resuscitation services, the introduction of high-tech methods and means of treatment.